PENGEMBANGAN OBJEK WISATA BERBASIS ANALISIS SWOT (JURNAL SPASIAL, 2016)
AbstrakThis study who understand the phenomenon of what has been experienced by the research subjects minsalnya behavior, perception, motivation, action. Respondents in this study are the Department of Tourism, visitors and the community immediately surrounding the attraction taking technique performed Snowball Sampling informants, informants and instruments used in this research is interview. The results of this study found that the existing tourist attraction with the theory of SWOT analysis as follows: 1) Strength (Strengths) owned tourist area is a natural beauty that is natural without the touch of human hands, and also can be an application of education for school children and the need, 2) weakness (weakness) of the area attractions that there is a lack of maintenance of the parties pengelolah in the beauty of this attraction than the level of accessibility that is less supportive and tourist sites away from the crowds, lack of promotion so that this region is not so much in the interest of visitors and investors 3) Opportunities (Opportunities) with the tourist areas can create new jobs for the community setempat.4) threats (threats) that pose a threat to the object region the rainy season makes access road is getting worse and landslides , The events that we do not want to be harmful to people and the government.Keywords:swot analysis pengembengan tourism management.